Tensile strength equation for HSS bracing members having slotted end connections. - Han, Sang-Whan (Earthquake engineering & structural dynamics.)
In the previous study, the authors investigated the effect of w/t ratios on the behaviour of bracing members under symmetric cyclic loading in compression and tension. In this study, 11 bracing members with slotted end sections made of cold-formed square hollow structural sections (HSS) were tested. The w/t ratios ranged from 8 to 28. Unlike the test results of other former studies obtained under compression-oriented cyclic loading, the results of this study showed that bracing members having a smaller w/t ratio (<14) had less deformation and less energy dissipation capacity, and a shorter fracture life compared with other specimens. Such inferior behaviour resulted from early fracture at the slotted end section. This study compares tensile strength obtained from the design equations in the AISC LRFD manual and Eurocode 3 using the actual strengths of the tested specimens. This study found that for preventing early fracture in HSS bracing members, design fracture strength should be larger than design yield strength. Design strength equations are proposed for bracing members in special concentrically braced frames (SCBF). The proposed design equations are verified by experimental tests conducted under symmetric cyclic loading in tension and compression using two HSS bracing members designed according to the proposed equation.